Optimalisasi Kegiatan Pengabdian kepada Masyarakat melalui Penyaluran Bantuan Kemanusiaan bagi Korban Banjir di Aceh Utara - Risna Dewi; Depita Kardiati; Revo Bayu Erlangga Saragih (Jurnal Pengabdian Masyarakat, 2026)
Flood disasters that repeatedly impact communities in North Aceh Regency demand rapid and well-coordinated humanitarian responses. This activity aimed to distribute humanitarian aid to flood-affected communities across 9 villages in 4 sub-districts of North Aceh Regency on December 31, 2025. The method employed a participatory and collaborative approach through direct distribution at affected locations, involving village apparatus and community leaders to ensure aid reached intended beneficiaries. The program was implemented through multi-stakeholder collaboration involving three partner institutions: Yayasan Semesta Rumah Kita, SMK YP 17 Cilegon, and LAZISNU. Aid distributed comprised 10 categories of items, including Qurans (150 copies as the first phase of a 5,000-copy target), basic food commodities, medicines, ready-to-eat food, children's milk, undergarments, prayer mats, sarongs, and mosquito repellent. The program successfully reached all 9 target villages with a distribution achievement of 100% of the planned locations. The results show that multi-stakeholder collaboration strengthens the effectiveness of aid distribution, increases accountability through direct community involvement, and strengthens the university's social engagement.